Pinter's Enigmatic World: Portrayal of Trapped Souls in his Selected Plays (Global Journal of Human-Social Science, 2023)
The world of Harold Pinter is a world of menace, confusion, uncertainty, and mystery. He has examined complex human relationships, communication breakdowns and post war frustrations as a playwright of 20th century. In his plays The Room, The Dumb Waiter, and The Caretaker he has explored the concept of trapped souls. These plays reflect the existential crisis of the characters, who are imprisoned in different types of physical, social, and psychological conditions. The character Rose is portrayed as a dedicated wife in the play The Room. Her life signifies her confinement as a partner of Bert in that shabby place. She is trapped in her existential condition. She treats the outside world as a threat and is satisfied in her situation. But finally, the room becomes a violent, brutal place for her. The Dumb Waiter delves into the psychological captivity of its protagonists, Ben and Gus, who operate as hit-men in a basement. In addition to being physically imprisoned, they are also existentially constrained as they struggle with the ridiculousness of their assignments and the enigmatic messages that the dumbwaiter delivers.
Keywords: uncertainty; trapped; existential crisis; violence; dilemma